Retroperitoneal Pleomorphic Rhabdomyosarcoma in Adult: A Rare Case Report - Martono, Budi; Inggriani, Sri (JBN (Jurnal Bedah Nasional); Vol 4 No 2 (2020): JBN (Jurnal Bedah Nasional), 2020)
Background: Rhabdomyosarcoma (RMS) is the most common type of soft tissue sarcoma in children, however, RMS is a rare malignancy in adults. Head and neck are the most common site for RMS, while intrabdominal RMS are rare in adults . Case: We present a rare case of a retroperitoneal abdominal mass, treated surgically with histopathology results of a retroperitoneal RMS. We discuss the clinical presentation, image findings, and treatment for this case. Conclusion: Intraabdominal tumours need to be identified quickly and precisely. CT scan or MRI can help clinicians to determine the staging, therefore plans the best treatment for the patient. In our case, surgery and radiotherapy showed promising outcome. The lack of literature and consensus on a standardized approach to systemic treatment and outcome in retroperitoneal pleomorphic RMS in adults makes our case a rare presentation of rhabdomyosarcoma and thus the need for reporting.